Exploring the landscape of thalassemia prevention: from screening strategies to economic impact - Jaafar, Safurah; Abd Rahim, Azrin Syahida; Abd. Rahim, Nour El Huda (The Athens Institute for Education and Research, 2024)
Thalassemia, a long-standing challenge for a century, continues to inflict substantial morbidity and mortality rates. Despite the absence of a comprehensive review on the economic aspects of prevention efforts, this examination illuminates a landscape rich with diverse, yet efficacious strategies aimed at curtailing national thalassemia burdens. Employing the meticulous methodologies outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020), an extensive search across various databases including Scopus, Web of Science, and others yielded a corpus of 5,425 potential articles. Encouragingly, numerous nations have witnessed remarkable declines in thalassemia prevalence subsequent to the implementation of intervention initiatives spanning several decades. Divergence emerges in screening methodologies, with the pace of reduction contingent upon the screening modality adopted, encompassing blood screenings of adolescents and antenatal mothers, and, in certain jurisdictions, termination of pregnancies. Financial considerations, though multifaceted and challenging to standardize, underscore the overarching conclusion that the costs associated with screening, while substantial, are outweighed by the economic benefits derived from diminished caseloads. Notably, selected countries have conducted costeffectiveness analyses bolstering the rationale for sustained investment in thalassemia screening and prevention endeavors. The findings underscore marked disparities in success rates, with jurisdictions embracing comprehensive and proactive prevention and control schemes inclusive of laboratory screening, counseling services, and termination of pregnancies emerging as exemplars of efficacy.